PENGARUH FASILITAS SERTA KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DOMESTIK OBJEK WISATA TAMAN AIR TIRTAGANGGA - Ni Luh Sintya Jayanti; Ni Nyoman Yulianthini (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of facilities and service quality either simultaneously or partially on customer satisfaction among domestic tourists at the Tirtagangga Water Park tourism object. The data analysis technique used is multiple linear regression analysis. The number of samples in this research is 150 people, the sample method used is purposive sampling method based on certain criteria. The results of this study are (1) Facilities and service quality have a significant influence on customer satisfaction of Tirtagangga Water Park attraction among domestic tourists, (2) Facilities have a positive and significant influence on customer satisfaction of Tirtagangga Water Park's customers among domestic tourists (3) Service quality has a positive and significant impact on customer satisfaction of Tirtagangga Water Park's customers among domestic tourists